If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(2+4x)-6x+8=-5(4-3x)
We move all terms to the left:
-5(2+4x)-6x+8-(-5(4-3x))=0
We add all the numbers together, and all the variables
-5(4x+2)-6x-(-5(-3x+4))+8=0
We add all the numbers together, and all the variables
-6x-5(4x+2)-(-5(-3x+4))+8=0
We multiply parentheses
-6x-20x-(-5(-3x+4))-10+8=0
We calculate terms in parentheses: -(-5(-3x+4)), so:We add all the numbers together, and all the variables
-5(-3x+4)
We multiply parentheses
15x-20
Back to the equation:
-(15x-20)
-26x-(15x-20)-2=0
We get rid of parentheses
-26x-15x+20-2=0
We add all the numbers together, and all the variables
-41x+18=0
We move all terms containing x to the left, all other terms to the right
-41x=-18
x=-18/-41
x=18/41
| 7(x+5)=-0.75(8x+40) | | 2w+5/6=(w+2/6)-2 | | 176+22x=16x-154 | | 2s+14=-14s | | w/4-13=-10 | | -4+b/9=-3 | | 5(u-4)-3u=-34 | | 1.2x+0.4=1.6 | | 8(7n-8)-n=-2n-7 | | 3(y+5)=4(y-7) | | 3(4-12a)=-4(6a+3) | | 5(m+3)=-7(5+2m)-6m | | x*0.33=180 | | w-8=-36 | | —h+4=-h+9 | | 24x-237=10x+267 | | 12(m-6)-4(m+5)=4-4m-12 | | -k-1=6 | | 20x+439=9x-232 | | -n-2=-11 | | -7n=-10n−9 | | -(8x-11)=5(x+2)-12 | | -8x=-4x+34 | | (x-17)(3)=-3 | | 2(x-10)=8(x+2) | | x2=36/12 | | m^=125 | | 4x-2/3=71/3 | | -1+7(a+6)=11(4a-3) | | 5r-3=-43 | | 3x*4x=480000 | | 10a+8=38 |